Budidaya Rumput Laut sebagai Sumber Pendapatan Masyarakat Wilayah Pesisir: bahasa indonesia - Sukrin, Sukrin; Agus Mokodompit, Eliyanti; Malik, Abdul (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
This research is based on the abundant potential of marine resources in the coastal area of Ronta Village, North Buton Regency, especially seaweed, which can be utilised to improve community welfare. But behind the potential, there are still many challenges faced by the community of Ronta Village, such as traditional cultivation techniques, limited capital, unoptimal market access, and climate change that affects productivity. On the other hand, the poverty rate in coastal areas is still a serious problem. The purpose of this research isto analyse the potential of seaweed cultivation as the main source of income for coastal communities in Ronta Village, North Buton Regency. The research method used was a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation studies. The sampling technique used purposive sampling which totalled 25 people from the coastal community. The results showed that capital assistance, experience, land area, seed quality, seaweed cultivation contributed significantly to the community's income, resulting in the opening of jobs, and improving living standards. This is evidenced by the average total cost of seaweed farming in one harvest season of Rp 3,647,022. Then the impact of the seaweed farming assistance programme in increasing farmers' income and one harvest season is Rp. 18,552,978 per harvest season. The conclusion of this research is that seaweed farming has great potential as an alternative source of income for coastal communities and can be an effective strategy in poverty alleviation in coastal areas.